OPTIMIZATION OF CHILDREN’S 10-11 YEARS DAILY MOTOR ACTIVITY IN CLUBS AT THE PLACE OF RESIDENCE - Rapatska I. B., (International Journal of Innovative Technologies in Social Science, 2021)
The study objective is to substantiate theoretically and to check the effectiveness of method of increasing the level of daily physical activity of younger adolescents 10-11 years in clubs at the place of residence by means of integrated moving games and to analyze their impact on the level of motor readiness of respondents, the functional state of the cardiovascular system and the level of health competencies.The results. After the introduction of the integrated methodology in the work of clubs at the place of residence, the level of children's daily motor activity increased statistically significantly (p ≤ 0.001) from very low to sufficient, indicators of the level of motor skills of respondents were statistically significant (p ≤ 0.001) and had significant dynamics. The cardiovascular system also had statistically significant improvements both boys and girls.The level of children's knowledge in the field of health in the context of this study increased significantly with high statistical reliability (p ≤ 0.001).Integrated mobile games, based on the principles of integrative physical education, individualize the physical load for each child, which affects the positive dynamics of increasing daily motor activity of children, the growth of motor fitness and functional status. The integration of cognitive and motor components of this methodology has also a positive effect on improving the level of health competencies of young adolescents 10-11 years.